Legal Reform of Zakat Management Based on Personal Data Protection Law in Indonesia - Rahmatullah, Indra; Suwadi, Pujiyono; Purwadi, Hari (Fakultas Syariah UINSI Samarinda, 2024)
This article proposes the idea of accommodating the concept of personal data protection in zakat management law in Indonesia. It is because the Zakat Management Organization and online platforms that facilitate zakat payments online still need legal certainty regarding collecting, using, and reporting personal data about zakat payers (muzakki). There needs to be more clarity on the types of muzakki's personal data that can be collected and reported by Zakat Management Organization and online platforms to the government, which creates the potential for a muzakki's personal data breach. This article uses normative legal research methods with statutory and conceptual approaches. In conclusion, a mutually agreed-upon personal data protection agreement is required between Zakat Management Organization, the online platform, and muzakki. Therefore, it is necessary to reform the zakat management law to be adaptive to personal data protection by amending Law Number 23 of 2011 concerning the Management of Zakat.